Dynamic reading techinique to motivate students to learn english as a second language at the tenth grades in Daniel O. Crespo High School - González Núñez, Dwight Elan Mauricio (UDELAS, 2015)
This study wukk orivude you a guide abouta what is happening in our educational enviroment now. Thus, this investigation will include a lot of important data that will offer meaningful information about why students are not getting the necessary English knowledge to be able to acquire English as a second language in high school.